Debating Archaeological Empiricism : The Ambiguity of Material Evidence - Hillerdal, Charlotta (Routledge Studies in Archaeology, 2015)
Cover -- Title -- Copyright -- Contents -- Introduction: Debating Archaeological Empiricism -- 1 Why 'The Death of Archaeological Theory'? -- Comment -- Comment -- 2 Archaeology and the Second Empiricism -- Comment -- Comment -- 3 Public Archaeological Challenges in the 2010s: Learning from Participatory Action in Practice -- Comment -- Comment -- 4 Students First, Please! -- Comment -- Comment -- 5 Archaeology Is History or It's History -- Comment -- Comment -- 6 Empirical Tensions in the Materialities of Time -- Comment -- Comment -- 7 Neo-empirical Mixtures -- Comment -- Comment -- Debating Archaeological Empiricism: Some Closing Comments -- Contributors -- Index.